Pitch-derived C coated three-dimensional CNTs/reduced graphene oxide microsphere encapsulating Si nanoparticles as anodes for lithium-ion batteries - Lee, Jae Seob; Jo, Beom Su; Park, Jin Sung; Cho, Jung Sang (Electrochimica Acta, 2025)
This study presents an innovative strategy for synthesizing a sophisticated three-dimensional conductive framework that contains well-dispersed silicon nanoparticles. This framework features silicon nanoparticles encapsulated by a composite of one-dimensional carbon nanotubes (CNTs), two-dimensional reduced graphene oxide (rGO), and amorphous carbon, all of which are further coated with a pitch-derived carbon (PDC) layer. This unique nanostructured anode was prepared from a one-pot spray drying process, heat-treatment and subsequent pitch-derived carbon coating. Combining 1D CNTs and 2D rGO nanosheets creates a 3D conductive network that can facilitate the electrochemical reaction kinetics. Furthermore, pitch-derived carbon coating at the interior and on the surface densified the electrode, ensuring both lithium-ion and electron transport and enhancing the Coulombic efficiency. Therefore, the composite plays the role of an effective mixed ionic and electronic conductor (MIEC), which can highly enhance the electrochemical performance of Si-based anode. Also, the volume expansion issues of silicon materials could be resolved by compositing with 3D conductive carbon matrix and reinforcing the structural robustness by coating with PDC layer, which could effectively alleviate the stress occurring from repetitive cycling. When used as the anode in lithium-ion batteries, the microspheres exhibited exceptional initial discharge/charge capacities of 3814/2791 mA h g–1 at 0.1 A g−1 with high Coulombic efficiency of 73.2 %, and demonstrated highly stable cycle performance, delivering a discharge capacity of 947 mA h g−1 after 350 cycles at a current density of 1.0 A g−1.
Keywords: Carbon coating; Carbon layers; Coulombic efficiency; Derived carbons; Ion batteries; Lithium ions; Reduced graphene oxides; Si nanoparticles; Silicon nanoparticles; Spray-drying; Carbon nanotube; Lithium-ion batteries; Reduced graphene oxide; Silicon; Spray drying